Menumbuhkan Minat Berwirausaha Sebagai Upaya Meningkatkan Ketahanan Ekonomi Keluarga di PAC Gerakan Pemuda Ansor Kecamatan Cipondoh, Kota Tangerang - Ahmad Yani Nasution; Nefo Indra Nizar; Ivan Putranto (Indonesian Journal of Society Engagement, 2022)
This service aims to provide training on Entrepreneurial Interests as an effort to increase family economic resilience after the Covid-19 period. Participants who took part in this PKM were members of the Sub-Branch Leadership (PAC) Gerakan Pemuda Ansor kec. Cipondoh, Tangerang. The method used is the method of Lectures, Discussions and Questions and Answers about the interests and efforts to improve the family's economy. The result is that the ability of quality soft skills is very much needed. These abilities include mindset, negotiation skills, and a positive attitude. This ability will be very useful in the world of work and in social interactions in general. Thus the interest in entrepreneurship as an effort to improve the family economy can be realized.